Usefulness of Ultrasound in Cardiorespiratory Arrest: About a case: Ultrasonido en el paro cardio -respiratorio (Universitas Medica, 2021)
High-risk pulmonary embolism thrombus is one of the causes of cardiorespiratory arrest with a non-fibrillae rhythm, where early diagnosis and treatment are essential to decrease mortality. During the last two decades the use of ultrasound has increased in different types of medical areas, which has led to the creation of protocols to unify concepts. One of these is the CAUSE protocol (Cardiac Arrest Ultrasound Exam), which allows a diagnostic approach to 4 causes of non-arrhythmogenic cardiorespiratory arrest (severe hypovolemia, tension pneumothorax, cardiac tamponade, and high-risk pulmonary embolism) using a projection of 4 chambers of the heart (apical or subxiphoid) and a thoracic projection through the second intercostal space in the mid-clavicular line. We present the case of a patient in cardiorespiratory arrest, who initially focused on the presence of acute coronary syndrome as the cause of findings of complete left bundle branch block on the electrocardiogram. However, after the use of ultrasound, the diagnostic perspective changes, finding indirect signs of pulmonary embolism, which led to changes in medical behavior.